2022
DOI: 10.47853/fas.2022.e4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different heating conditions on protein composition in each muscle type of yellowtail (Seriola quinqueradiata)

Abstract: To clarify the factors influencing the physical properties of fish after heat treatments, we investigated changes in the properties of proteins in the dorsal ordinary and dark muscle of yellowtail (Seriola quinqueradiata) heated under different conditions commonly used for the purposes of food hygiene. High-temperature/short-time heating (85℃ for 90 s and 75℃ for 60 s) affected the protein solubility more than low-temperature/long-time heating (63℃ for 30 min). Sodium dodecyl sulphate-polyacrylamide gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Chan et al [82] showed that thermal treatment causes thermal aggregation, which reduces protein solubility as more hydrophobic surfaces of the protein become exposed to water. This is in agreement with Furuta et al [77] who showed that heating fish protein at 75 °C for 1 min or at 95 °C for 1.5 min significantly reduced protein solubility. Enzyme hydrolysis reactions are typically quenched at temperatures above 80 °C for at least 15 min [8,[83][84][85], which is sufficient time to lose protein to thermal aggregation.…”
Section: Protein Loss To Emulsion and Sludgesupporting
confidence: 93%
See 1 more Smart Citation
“…Chan et al [82] showed that thermal treatment causes thermal aggregation, which reduces protein solubility as more hydrophobic surfaces of the protein become exposed to water. This is in agreement with Furuta et al [77] who showed that heating fish protein at 75 °C for 1 min or at 95 °C for 1.5 min significantly reduced protein solubility. Enzyme hydrolysis reactions are typically quenched at temperatures above 80 °C for at least 15 min [8,[83][84][85], which is sufficient time to lose protein to thermal aggregation.…”
Section: Protein Loss To Emulsion and Sludgesupporting
confidence: 93%
“…The presence of unhydrolysed protein in the sludge is typical of enzyme hydrolysis processes where not all substrate is accessible to enzyme or soluble during the enzymatic reaction [49,60,75,76]. Different studies have shown that the denaturation temperature of fish protein generally ranges from 65 to 95 °C [77][78][79][80][81][82]. Chan et al [82] showed that thermal treatment causes thermal aggregation, which reduces protein solubility as more hydrophobic surfaces of the protein become exposed to water.…”
Section: Protein Loss To Emulsion and Sludgementioning
confidence: 99%